FILSAFAT ILMU SEBAGAI PEMBENTUK KARAKTERISTIK PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA - I Made Dharma Atmaja (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2020)
Mathematics teachers have different characteristics in the presentation material, which may determine different interpretations in students' perspectives. Mathematical learning media can be created by using writing, audio, visuals, or even a combination of all. If the selection of mathematics learning media is carried out correctly, it will greatly help learning interaction in the classroom. Philosophy of science and education have a large role in shaping the characteristics of the media of mathematics learning. In the field of science and education, several aspects and dimensions are the basis for making mathematics learning media, namely aspects of ideas and facts, as well as abstract and concrete dimensions both theoretically and practically. Based on thinking, education, and expertise in the development of mathematics learning media, if summarized in accordance with practical objectives, it will be able to create practical values that are in accordance with the needs or learning outcomes.